Slope Stability Analysis for Sections in Al-Furat River by Finite Element Method - H. Abdul Kareem, Ahmed (Iraqi Journal of Civil Engineering, 2010)
AbstractThe aim of this study is to analyze the slope stability for sections in Al-Furat River where engineering construction build on it, when a sudden decrease in the river water level happens. Two sections were chosen from the river in the area located about 35 km away from Ramadi city called Tel Aswad where undisturbed samples are taken and laboratory tests are done to obtain the soil parameters which are used in Geo-Slope program. The finite element method was applied in this study with elastic-plastic soil model. The analysis results show that the sections slope chosen from the river are stable. The second purpose of this analysis to reduce the risk of using earth structures when engineering construction build on it. Also, it is clear that the values of factor of safety calculated by the FEM are low compared with limit equilibrium methods.